DESCRIPTIVE PHYSICAL OCEANOGRAPHY : AN INTRODUCTION - Talley, Lynne D.; Pickard, George L.; Emery, William J.; Swift, James H. (Academic Press, 2011)
The sixth edition of Descriptive Physical Oceanography provides an introduction to descriptive physical oceanography for advanced undergraduates and graduate students. The emphasis is on large-scale oceanography, based mainly in observations, with some topics from waves and coastal oceanography also included. Topics include the physical properties of seawater, heat and salt budgets, instrumentation, data analysis methods, introductory dynamics, oceanography and climate variability of each of the oceans and of the global ocean, and brief introductions to the physical setting, waves, and coastal oceanography.